2022
DOI: 10.1002/mde.3670
|View full text |Cite
|
Sign up to set email alerts
|

Innovation efficiency and firm performance in a benchmarking context

Abstract: This paper examines the effect of innovation efficiency on firm performance using the Greek version of the Community Innovation Survey (CIS) 2012-2014 and employs a dataset of 1,274 innovative manufacturing firms. Introducing a data envelopment analysis (DEA)-type benchmarking strategy with non-continuous knowledge inputs, the main findings suggest that innovation efficiency, although does not exert a direct impact on firm performance, moderates the relationship between the internally generated knowledge and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…For example, Erdin and Ça glar (2022) and Feng et al (2021) showed that Greece's performance in using innovation resources efficiently to generate innovation outputs was below the average. Kanellopoulos and Tsekouras (2023), who analyzed the micro level and the dataset of 1274 innovative manufacturing firms, found that Greek companies could produce the same innovation outputs using significantly fewer innovation resources. To be precise, Aytekin et al (2022) estimated that Greece lacks knowledge, technology, and creative output and should be able to produce 3.14% more outputs with the current input levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Erdin and Ça glar (2022) and Feng et al (2021) showed that Greece's performance in using innovation resources efficiently to generate innovation outputs was below the average. Kanellopoulos and Tsekouras (2023), who analyzed the micro level and the dataset of 1274 innovative manufacturing firms, found that Greek companies could produce the same innovation outputs using significantly fewer innovation resources. To be precise, Aytekin et al (2022) estimated that Greece lacks knowledge, technology, and creative output and should be able to produce 3.14% more outputs with the current input levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ref. [56] investigated the relationship between external innovation spillovers and firm performance and found no significant effect between these variables.…”
Section: Regional and Urban Economics Perspectivementioning
confidence: 99%